ESTUDIOS CITONUCLEOLARES DE LOS TUMORES ENCEFALICOS II NUCLEOLOS DE EPENDIMOMAS - GONZALEZ GUZMAN, IGNACIO (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1942)
A review of the morphologic features previously observed in exptl tumefaction of the brain
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, CITONUCLEOLARES, TURNORES, ENCEFALICOS, NUCLEOLOS, EPENDIMOMAS; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA